A new technique for cross-sectional density profiling of extruded foods by X-ray scanning. (April 2016) - Kowalski, Ryan J.; Morrow, C.D.; McDonald, Armando G.; Ganjyal, Girish M.
Graphical abstract: Highlights: Explores the feasibility of a new density characterization technique for foods. Compares the new density method to current density assessment methods. Applies new density method to extruded products to examine density along their cross-sections. Demonstrates the technique's usefulness in quality assurance. Abstract: A wide variety of snack and cereal products are manufactured using extrusion. Often, these products are produced by direct expansion upon exiting the extruder by utilizing a raw material that is predominately starch. The density of extruded food products is an important quality parameter that determines its sensory and physical characteristics, as well as the appropriate packaging. Direct expanded products often shrink differentially with cooling after their initial expansion resulting in different localized densities within a product. We developed a novel technique to determine these localized cross-sectional density differences within an extruded product using an X-ray density profiler. Commercial, direct expanded products were characterized using this technique. All products demonstrated significantly higher densities near the edge, compared to the center of the product. Density profile data provided a means to rapidly characterize and image density variations axially and radially, offering a viable alternative to currently used density methods, while also providing more information. Different extruded foods can have significantly different localized densities. SEM images confirmed that the density differences in the products are visible through a smaller, more collapsed cell structure near the edge compared to the center. X-ray density profiling can provide insight into the eating characteristics of extruded products and will be a useful tool in product development and quality assurance.